MITOS MBAH BREGAS DI DUSUN NGINO DESA MARGOAGUNG SEYEGAN SLEMAN YOGYAKARTA (STUDI TERHADAP KLASIFIKASI, PANDANGAN DAN FUNGSI MITOS) - Iftahuul Mufiani (UIN Sunan Kalijaga Yogyakarta, 2015)
Indonesia consists of various communities that have distinctive culture. One of diversecultures in Indonesia that has its uniqueness on Javanese culture particularly on kejawenelements, is in around Sleman, Yogyakarta. Some people in Ngino, Margoagungbelieved in the kejawen that utilized myth in everyday life both in tradition and arts.The myth in Javanese society is so profound; myth becomes an important aspect ofreligious system in kejawen. Considering the importance of myth among Javanese, thisstudy discusses the myth of Mbah Bergas in Margoagung. The existence of MbahBergas gives an indirect infl uence on religiosity among Muslims in Ngino. The infl uenceof the myth is manifest among the people of Ngino in their cultural and social life.